2017
DOI: 10.1515/cait-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Machine Translation: Phrase-Based, Rule-Based and Neural Approaches with Linguistic Evaluation

Abstract: In this article we present a novel linguistically driven evaluation method and apply it to the main approaches of Machine Translation (Rule-based, Phrase-based, Neural) to gain insights into their strengths and weaknesses in much more detail than provided by current evaluation schemes. Translating between two languages requires substantial modelling of knowledge about the two languages, about translation, and about the world. Using English-German IT-domain translation as a case-study, we also enhance the Phras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
15
1
1
Order By: Relevance
“…However, when tested in the reverse translation direction (i.e., English-to-German), a commercial NMT engine becomes the winner as far as term translation is concerned. In a similar experimental setup, Macketanz et al [28] reported that their PB-SMT system outperformed NMT on terminology translation on both in-domain (IT domain) and general domain test suites in an English-to-German translation task. Specia et al [29] carried out an error annotation process using the multidimensional quality metrics (MQM) error annotation framework [30] in an MT post-editing environment.…”
Section: Terminology Translation In Pb-smt and Nmtmentioning
confidence: 98%
See 1 more Smart Citation
“…However, when tested in the reverse translation direction (i.e., English-to-German), a commercial NMT engine becomes the winner as far as term translation is concerned. In a similar experimental setup, Macketanz et al [28] reported that their PB-SMT system outperformed NMT on terminology translation on both in-domain (IT domain) and general domain test suites in an English-to-German translation task. Specia et al [29] carried out an error annotation process using the multidimensional quality metrics (MQM) error annotation framework [30] in an MT post-editing environment.…”
Section: Terminology Translation In Pb-smt and Nmtmentioning
confidence: 98%
“…For example, Huang et al [36] investigated term translation in a PB-SMT task and observed that more than 10% of high-frequency terms were incorrectly translated by their PB-SMT decoder, although the system's BLEU score was quite high, i.e., 63.0 BLEU. One common event in the above papers [27][28][29]31,32,35,36] was that the authors carried out a human evaluation in order to measure terminology translation quality in MT, which, as mentioned earlier, is subjective and a slow and expensive process. In this paper, we present a faster and less-expensive evaluation strategy for preparing a gold standard, based on which our metric, TermEval, can measure terminology translation quality in MT.…”
Section: Terminology Translation In Pb-smt and Nmtmentioning
confidence: 99%
“…The machine Translation process can be broadly classified into the following approaches Machine Translation process can be broadly classified into Rule-based [5] [6] [7], Statisticalbased [8][9] [10] and Neural-based approaches [5] [11] [12]. For these approaches, the translation system is trained with a bilingual text corpus to get the desired output.…”
Section: Figure 1 Processing Of Rule-based Approachesmentioning
confidence: 99%
“…The advantages of NMT and its challenges have been investigated from different angles in recent work (Koehn and Knowles, 2017;Toral and Sánchez-Cartagena, 2017;Farajian et al, 2017;Macketanz et al, 2017;Castilho et al, 2017a;Klubička et al, 2017;Bentivogli et al, 2018;Isabelle et al, 2017;Popović, 2017;Forcada, 2017;Castilho et al, 2017b;Junczys-Dowmunt et al, 2016;Klubička et al, 2018;Shterionov et al, 2017;Burchardt et al, 2017, inter alia), however, studies on interactive NMT, especially user studies involving human post-edits of NMT outputs, have so far not been presented.…”
Section: Related Workmentioning
confidence: 99%